The Ceratocanthinae of Madagascar and Comoro Islands: a revision of the genera Synarmostes and Goudotostes, and of the flightless Philharmostes, with description of 64 new species (Coleoptera: Scarabaeoidea: Hybosoridae) - Ballerio, Alberto (Fragmenta entomologica, 2021)
Abstract The Ceratocanthinae (Coleoptera Scarabaeoidea Hybosoridae) genera Synarmostes Germar, 1843 Goudotostes Paulian, 1979, and Philharmostes Kolbe, 1895 (partim) are revised. The genera Synarmostes and Goudotostes, endemic to Madagascar and Comoro Islands, score respectively 24 species, 18 occurring in Madagascar and six in the Comoro Islands (20 of them new to science: Synarmostes aes sp. nov., Synarmostes annamariae sp. nov., Synarmostes beankae sp. nov., Synarmostes benaraensis sp. nov., Synarmostes bekaraokae sp. nov., Synarmostes caterinae sp. nov., Synarmostes chonguimontis sp. nov., Synarmostes compactus sp. nov., Synarmostes dapaniensis sp. nov., Synarmostes eugenii sp. nov., Synarmostes fortis sp. nov., Synarmostes grinteri sp. nov., Synarmostes karthalaensis sp. nov., Synarmostes lavasoae sp. nov., Synarmostes makirovanae sp. nov., Synarmostes monoculus sp. nov., Synarmostes occidentalis sp. nov., Synarmostes parrilloi sp. nov., Synarmostes separatus sp. nov., and Synarmostes zahamenae sp. nov.) and 33 species, two of them occurring in the Comoro Islands and the remaining in Madagascar (32 of them new to science: Goudotostes andohahelae sp. nov., Goudotostes andreonei sp. nov., Goudotostes angelii sp. nov., Goudotostes antsahabensis sp. nov., Goudotostes electrimontis sp. nov., Goudotostes elegans sp. nov., Goudotostes fisheri sp. nov., Goudotostes hirtellus sp. nov., Goudotostes insularis sp. nov., Goudotostes laevis sp. nov., Goudotostes lapidisilvae sp. nov., Goudotostes litoralis sp. nov., Goudotostes lokobensis sp. nov., Goudotostes mayottensis sp. nov., Goudotostes masoalae sp. nov., Goudotostes montanellus sp. nov., Goudotostes orangeanus sp. nov., Goudotostes parvus sp. nov., Goudotostes phantasticus sp. nov., Goudotostes pittinoi sp. nov., Goudotostes rafanomezantsoai sp. nov., Goudotostes rajemisonae sp. nov., Goudotostes rakotonirinai sp. nov., Goudotostes ramamonjisoae sp. nov., Goudotostes ranaivoi sp. nov., Goudotostes randrianirinai sp. nov., Goudotostes rasoamananae sp. nov., Goudotostes rugatulus sp. nov., Goudotostes siccaesilvae sp. nov., Goudotostes similis sp. nov., Goudotostes simplicipennis sp. nov., and Goudotostes trapeticollis sp. nov.). Finally, the genus Philharmostes, shared with Continental Africa but absent from Comoro Islands, is here revised only partly. Only the 12 flightless species occurring in Madagascar are revised, all them endemic and new to science (Philharmostes acutus sp. nov., Philharmostes apterus sp. nov., Philharmostes centralis sp. nov., Philharmostes fereocellatus sp. nov., Philharmostes indri sp. nov., Philharmostes manomboensis sp. nov., Philharmostes metallicus sp. nov., Philharmostes nelsoni sp. nov., Philharmostes ornatulus sp. nov., Philharmostes rotundatus sp. nov., Philharmostes scapulatus sp. nov., and Philharmostes schweikerti sp. nov.). The volant species of Philharmostes will be the subject of a future paper. With the new species here described Madagascar scores a total of 81 species of Ceratocanthinae, all them endemic, becoming the richest country in the world with respect to Ceratocanthinae diversity. The majority of the Ceratocanthinae species dealt with this paper are flightless (65 on a total of 69). All species have been found in forested habitats, the majority of them (53 species) in rainforests and 17 species in dry deciduous forests. Three species have been found in nests of Nasutitermes sp. (Isoptera). Some remarks on eye development are provided. In some species of all the genera it is hypothesized the presence of a vestigial dorsal ocular area. A key to all species, distribution maps and photos of the habitus and the male genitalia of all species are provided.